A Network Meta-Analysis of the Dose–Response Effects of Dapagliflozin on Efficacy and Safety in Adults With Type 1 Diabetes - Li, Yinhui; Li, Hui; Dong, Liming; Lin, Dandan; Xu, Lijuan; Lou, Pengwei; Zang, Deng; Wang, Kai; Ma, Li (Frontiers in Endocrinology, 2022)
Background: Many patients with type 1 diabetes (T1DM) do not achieve the glycemic target goal with insulin treatment. In this study, we aimed to evaluate the efficacy and safety of add-on different dosage of dapagliflozin to insulin therapy in patients with T1DM. Methods: We conducted direct and indirect network meta-analysis useing Bayesian models and ranked hypoglycemic agents via mixed treatment comparison. We used data from the PubMed, Embase, The Cochrane Library, Web of Science, China biomedical database (CBM), Chinese journal full-text database (CNKI), WANFANG DATA, WEIPU DATA. Randomized controlled trials (RCTs) involving patients with T1DM treated with insulin and add-on dapagliflozin 5mg or dapagliflozin 10mg from January 2012 to June 2021 were included in this study. 13 RCTs with 10701 subjects were divided into the following groups: insulin alone, insulin+ dapagliflozin 5mg, and insulin+ dapagliflozin 10mg. Results: Dapagliflozin exhibited reductions in glycated haemoglobin (HbA1c), total insulin daily dose (TDD), and body weight in a dose-dependent manner. Both dapagliflozin 5mg and 10mg did not induce hypoglycemia, severe hypoglycemia, but increased the risk of diabetic ketoacidosis (DKA) and genital infection. Dapagliflozin 10mg did not increase the risk of urinary tract infection, Dapagliflozin 5mg increased the risk of urinary tract infection. Conclusions: Dapagliflozin 10mg could achieve a better outcome on efficacy and could not increase the risk of hypoglycemia and urinary tract infection, although it may induce a higher risk of DKA and genital infection, there were not significant difference between dapagliflozin 10mg and 5mg. Thus, our results suggest that dapagliflozin 10mg has a high probability of being ranked prior as an adjunctive therapy to insulin in patients with T1DM.